“Aggravated, everyday aggravated—everyday”: senseMaking to truth tell, talkback and find belonging in educational research - Clark, Emily B. (Frontiers in Education, 2023)
This article explores an analytical, reflexive, epistemological, and liberatory research approach I call senseMaking. This article draws upon data from a larger narrative study of participants who work(ed) and/or learn(ed) in self-contained special educational environments in New York City. I use creative writing and quilting as examples of senseMaking tools to complicate and question the deficit-laden narratives and research that currently inform decision making about special education and traditional methods of educational research.